Operation strategies for a flexible megawatt scale electrolysis system for synthesis gas and hydrogen production with direct air capture of carbon dioxide. Issue 2 (16th December 2022) - Tomberg, Marius; Heddrich, Marc P.; Ansar, S. Asif; Friedrich, K. Andreas
Abstract : An in-depth investigation of operation strategies for hydrogen and synthesis gas production using reactors with solid oxide cells. Abstract : Among electrolyzers, electrolysis systems with solid oxide cell (SOC) reactors can operate at the highest efficiency due to low electrochemical losses and the utilization of waste heat for the evaporation of water. Additionally, SOCs can be operated not only in H2 O electrolysis mode, but also in CO2 electrolysis and co-electrolysis mode, resulting in high flexibility. In this contribution, developed operation strategies for the transient operation of MW-scale electrolysis systems with solid oxide cells are presented. By applying these strategies, it is shown that systems with SOCs can be operated more transiently than usually assumed. The investigations were carried out in the context of a megawatt scale flexible electrolysis system concept with carbon dioxide capture from air, where the process system would consist of twelve reactors with a nominal load of 80 kW. Concepting, parameterization and simulation rely on DLR's experiments on an actual 80 kW SOC reactor. Crucial and efficient operation points were defined and transitions between these were established by comparison of different strategies and control approaches. The simulation results show that fast and robust transients are possible. For example, the start-up time from hot-standby to 70% of nominal load could be decreased by a factor of 5. The start-up time to nominal load operation was reduced by 20%, while the temperature gradients were reduced by a factor of 2. Furthermore, by taking advantage of the modular nature of state-of-the-art reactors, fast power modulation can be achieved.